Evaluation of Appropriate Dividend Payout Ratio at PT. Telekomunikasi Indonesia, Tbk. - Sulistyo, Annisa Rahma Nur; Sumirat, Erman (The Indonesian Journal of Business Administration, 2015)
Abstract.PT. Telekomunikasi as one of state-owned enterprise and telecommunications service provider company in Indonesia has been privatized since 1995. As a privatized company, PT. Telekomunikasi Indonesia distributes dividends to shareholders, both the government and the public shareholders. All this time, PT. Telekomunikasi Indonesia paid dividend as the rest of net profit after allocated for the investment. Along with the increasing net profit every year, it also generated higher dividend payout ratio in 2004-2013. Beside the increasing net profit, government as the major shareholders wanted high dividend from PT. Telekomunikasi Indonesia to fulfill the Indonesian Budget. The purpose of this final project is to know how much the appropriate dividend payout ratio of PT. Telekomunikasi Indonesia with analyze what are the determinants. In order to know what are the the determinants of dividend payout ratio, by using multiple linier regression, the result is that return on equity, size, free cash flow from equity, debt to equity ratio, growth, and risk effect high dividend payout ratio. Every company has different capacity to pay dividend based on what stage the company is. To know company stage, there are three factors to analyze, external fund, internal fund, and capacity to pay dividend. PT. Telekomunikasi Indonesia has increasing dividend payout ratio from 2004-2013 and use more internal fund (equity) than external fund (debt). Thus PT. Telekomunikasi Indonesia is in mature growth company. The next research is analyze appropriate dividend payout ratio PT. Telekomunikasi that compare to the competitors and worldwide telecommunication service provider companies. Using data dividend payout ratio from 2004-2013, dividend payout ratio trend for telecommunication industry is between 50% - 69% because of there are some investment opportunities in the future. With the appropriate dividend payout ratio, PT. Telekomunikasi Indonesia has to maintain the investment opportunities to make the company sustainable.Keywords: Dividend payout ratio; PT. Telekomunikasi Indonesia, Tbk.